Perception of Dynamic Social and Non-social Stimuli in Preterm and Full-term Children: Neurocognitive Correlates in Early Childhood - Chegodaev, D; Pavlova, P; Pavlova, N V (KnE Life Sciences, 2018)
Preterm birth is the leading cause of newborn deaths in almost all countries around the world. Whilst survivors encounter severe motor, cognitive and behavioral impairments during infancy or later in their lives, the studies of the recent years have demonstrated that the social development serving a basis for learning and cognition of the environment in human infants can be severely affected even in normally developing preterm born children (gestational age < 37 weeks). The current article presents a discussion on the behavioral as well as the neuroimaging aspects of the social maturation in preterm and full-term children, depicting complexity of the impairments and focusing on the involved brain structures. Further, authors perform the design of the longitudinal study of social and non-social perception in early childhood, implemented on the base of the Laboratory for Brain and Neurocognitive Development (Ural Federal University). Keywords: prematurity, social development, early childhood, neurocognitive correlates